Revision total hip arthroplasty with metal on metal bearing for ceramic bearing fractures - Park, Kyung Soon; Chan, Chee Ken; Kim, Sung Kyu; Li, Qing Song; Im, Chae Jin; Yoon, Taek Rim (Elsevier, 2019)
Background: Due to concern of potential metallosis caused by residual microscopic ceramic particles, metal-on-metal (MoM) bearing is deemed undesirable in revision total hip arthroplasty (THA) for ceramic bearing fracture. We determined whether MoM bearing is suitable to be used in revision THA for ceramic fractures and also evaluated whether this treatment increases serum iron levels compared with MoM bearing revision THA for polyethylene failure. Methods: Between 2006 and 2012, 22 patients underwent revision surgery using MoM bearing (28 mm femoral head in 18 hips and 32 mm in 4 hips) for ceramic bearing fracture and followed average 52.1 months. We assessed radiological parameter and functional outcome using Harris hip score (HHS) and WOMAC score. Also, serum cobalt (Co) and chromium (Cr) blood tests were performed and compared with the result obtained from age, sex- and follow-up duration-matched patients with MoM revision THA for failed polyethylene bearing. Results: The mean HHS improved from 60.6 preoperatively to 90.3 at final follow-up. There were no changes in cup position, progression of osteolytic lesions, and measurable wear of MoM bearing articulation at final follow-up radiographs. There was one case of recurrent dislocation after surgery, which was treated with greater trochanter distal advancement and one case of deep infection, which underwent two-stage revision. Mean serum Co level (1.7 vs. 1.4 μg/dl; p = 0.211) and Cr level (0.70 vs. 1.01 μg/dl; p = 0.327) showed no significant difference. Conclusions: MoM articulation with liner cementation into the acetabular cup along with total synovectomy can be chosen in revision surgery for ceramic fracture with good midterm follow-up. However, the use of MoM bearing is indicated when the stem and metal shell can be retained and ceramic on ceramic or ceramic on polyethylene bearing cannot be selected. Also long-term outcome needs to be further evaluated. © 2018